The impact of bone morphology on the outcome of the pivot shift test: a cohort study - Thomas Branch; Shaun Stinton; Adrija Sharma; Frederic Lavoie; Christian Guier; Philippe Neyret (BMC Musculoskeletal Disorders, 2017)
Abstract Background The presence of a positive pivot shift after surgical repair of the ACL is considered an important indicator of a failed reconstruction. The ability to predict the result of a pivot shift test after an ACL reconstruction using variables that can be measured prior to surgery could provide an indication of which patients may be at-risk of a poor surgical outcome.The purpose of this study was to determine whether structural characteristics of the femur and tibia, measured using plain radiographs, were associated with the result of the pivot shift test in unilateral ACL reconstructed patients. Methods Sixteen patients who had undergone unilateral ACL reconstruction were divided into two groups based on the results of manual pivot shift testing: 1) Pivot group; and 2) No pivot group. All patients had standing true lateral radiographs of both knees. Structural measurements of the tibia and femur were made on both knees. In addition, two new variables were created to describe the tibiofemoral mismatch: 1) Femur Tibia Size Ratio (FTSR); and 2) Tibia to Posterior Femoral Condyle Ratio (TPFCR). These measures were compared within groups and between groups. Results None of the individual structural characteristics were significantly different when compared between groups. No individual structural characteristics had a significant association with the presence of a positive pivot shift. When a between-group analysis was performed, both the FTSR (p < 0.03) and the TPFCR (p < 0.01) were significantly different between the Pivot group and the No Pivot group. A larger FTSR ratio, or a larger femur relative to the tibia, was associated with a positive pivot shift. A smaller TPFCR ratio, or a smaller tibial depth relative to the depth of the lateral posterior femoral condyle, was associated with a positive pivot shift. Conclusions Structural characteristics in the lateral femoral condyle and lateral tibial plateau were found to be associated with the presence of a positive pivot shift. These characteristics could separate between patients in the Pivot group and the No Pivot group. Two indices, the FTSR and the TPFCR, provided better predictive value than individual characteristics in identifying patients with a knee that was structurally “at-risk” for developing a positive pivot shift.